Manual therapies for posterior thigh muscles enhanced ten-repetitions maximum test performance and hip flexibility in young soccer players - Rios Monteiro, E.; Victorino, A.; Muzzi, R.; Cesar de Oliveira, J.; Cunha, M. (Perceptual and Motor Skills, 2021)
This study investigated how different manual therapies applied to the posterior thigh muscles affect the ten-repetitions maximum performance test (10 RM) and hip flexion range-of-motion among young soccer players. Seventeen non-professional male soccer players performed the 10RM and range of motion pre-testing, and, in separate laboratory visits, they underwent three different experimental activities presented to each participant in a randomized order: (a) rest control activity with no intervention, (b) manual massage, and (c) muscle energy. Comparing pre-testing performances to repeated tests after each intervention condition, participants increased their maximum load lift on the 10-repeitions maximum test following manual massage and muscle energy interventions (p < 0.05), but not following the control condition. They also increased their hip range-of-motion on flexibility testing following manual massage and muscle energy (p < 0.05), but not following the control condition. Thus, both manual massage and muscle energy therapies applied to the posterior thigh were beneficial to performance. This finding has clear implications when preparing athletes for competition.